Implementasi Kampus Hijau: Aplikasi Teknologi QR Code untuk Pengenalan Jenis Vegetasi di Lingkungan Kampus - Sri Kasmiyati; Andreas B.A. Sukmana; Sucahyo Sucahyo; Desti C. Cahyaningrum; Susanti P. Hastuti; Cocok A.M. Berutu; Risky H. Poluan; Natalia R. Keliat; Risya P. Situmorang; Elizabeth B.E. Kristiani; V. I. Meitiniarti; Rully A. Nugroho; Agna S. Krave (LPPM Uncen, 2026)
The high diversity of tree and shrub that were deliberately planted in the campus environment, is a proof of Satya Wacana Christian University's (UKSW) commitment in implementing the green campus concept. This Community Service aims to assist UKSW as a partner, in providing comprehensive, educational, and accessible information regarding vegetation identity in the campus environment for all academics and visitors.Those information is presented in the form of a tree identity board containing the local name, scientific name, international name, and QR code to access a website which contains comprehensive information about each type of vegetation, called